IMPLEMENTASI SIMRS SEBAGAI STRATEGI MENINGKATKAN INCOME RSUD MIMIKA - Alexander King; Purwadhi, Purwadhi; Ign. Wiseto P. Agung (Bajang Institute, 2025)
The Hospital Management Information System (SIMRS) is a vital tool in supporting efficient, integrated, and data-driven healthcare services. This study aims to evaluate the implementation of SIMRS at RSUD Kabupaten Mimika using the Human, Organization, and Technology – Fit (HOT-Fit) Model. The model assesses the alignment and readiness across the dimensions of technology (input), human and organizational processes, and the resulting system benefits (output). This research employed a qualitative approach using in-depth interviews, observations, and document analysis. Data were collected from seven key informants across primary service units and three triangulated informants from the quality management, human resources, and training divisions. Thematic analysis was conducted based on the HOT-Fit framework. The findings indicate that in terms of technology, the system still faces technical issues such as slow performance, limited data correction features, and the absence of a fully realized paperless culture. In the human dimension, user competence remains uneven, with limited ongoing training and no standardized system for assigning SIMRS responsibilities. From the organizational perspective, there is a lack of standardized SOPs, weak inter-unit coordination, and the absence of a dedicated SIMRS management team. Nevertheless, from the benefit/output dimension, SIMRS has contributed positively to increasing hospital revenue and service efficiency, although data utilization for decision-making remains limited. This study recommends strengthening internal policies, implementing continuous training, upgrading technology infrastructure, and conducting regular evaluations to ensure the sustainability and optimization of the system. The findings may serve as a policy reference and practical insight for other hospitals implementing or planning to implement SIMRS